Balancing Work and Life in a Virtual World: the Impact of Boundary Management, Virtuality, and Climate on Organizational Identification - (:unkn) unknown (My University, 2014)
Rooted in Boundary theory, this study extends recent research which suggests boundary management is a multi-dimensional process that can be broken into clusters of cross-role interruptions, role identity centrality, and boundary control (Kossek, Ruderman, Braddy, & Hannum, 2012). In addition, the study identifies relationships between these boundary management clusters, virtuality, organizational climate supporting work-home boundary customization, and organizational identification. This research also considers how the modern-day challenge of virtual work arrangements influences boundary control and perceptions of a supportive organizational climate. Finally, the study examines the relationships of boundary control and climate to employees' organizational identification. Findings indicate that Kossek et al.'s boundary management clusters can be replicated and influenced by virtuality, and one cluster was positively related to organizational climate and identification. In addition, virtuality was positively related to perceptions of a supportive organizational climate for customizing work-home boundaries, and negatively related to perceived boundary control. Finally, organizational climate supportive of customization of boundaries was positively related to organizational identification.
Keywords: Boundary Management; Organizational Climate; Organizational Identification; Virtuality